Impact of Virgin Olive Oil and Phenol-Enriched Virgin Olive Oils on the HDL Proteome in Hypercholesterolemic Subjects: A Double Blind, Randomized, Controlled, Cross-Over Clinical Trial (VOHF Study) - Pedret, Anna (PLoS One, 2015)
The effects of olive oil phenolic compounds (PCs) on HDL proteome, with respect to new aspects of cardioprotective properties, are still unknown. The aim of this study was to assess the impact on the HDL protein cargo of the intake of virgin olive oil (VOO) and two functional VOOs, enriched with their own PCs (FVOO) or complemented with thyme PCs (FVOOT), in hypercholesterolemic subjects. Eligible volunteers were recruited from the IMIM-Hospital del Mar Medical Research Institute (Spain) from April 2012 to September 2012. Thirty-three hypercholesterolemic participants (total cholesterol >200mg/dL; 19 men and 14 women; aged 35 to 80 years) were randomized in the double-blind, controlled, cross-over VOHF clinical trial. The subjects received for 3 weeks 25 mL/day of: VOO, FVOO, or FVOOT. Using a quantitative proteomics approach, 127 HDL-associated proteins were identified. Among these, 15 were commonly differently expressed after the three VOO interventions compared to baseline, with specific changes observed for each intervention. The 15 common proteins were mainly involved in the following pathways: LXR/RXR activation, acute phase response, and atherosclerosis. The three VOOs were well tolerated by all participants. Consumption of VOO, or phenol-enriched VOOs, has an impact on the HDL proteome in a cardioprotective mode by up-regulating proteins related to cholesterol homeostasis, protection against oxidation and blood coagulation while down-regulating proteins implicated in acute-phase response, lipid transport, and immune response. The common observed protein expression modifications after the three VOOs indicate a major matrix effect. TRIAL REGISTRATION: International Standard Randomized Controlled Trials ISRCTN77500181.